Production of monoclonal antibody against oxytetracycline for developing enzyme-linked immunosorbent assay (ELISA) test kit, 2nd year - Nanthika Khongchareonporn (Chulalongkorn University, 2015)
ได้รับทุนอุดหนุนการวิจัยจากเงินอุดหนุนทั่วไปจากรัฐบาล ประจำปีงบประมาณ 2558